Pengaruh Intangible Asset Value, Struktur Kepemilikan,Dan Kinerja Keuangan Terhadap Nilai Perusahaan(Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa EfekIndonesia tahun 2011- 2014)SKRIPSI - Isnaini, Nurul; , Dr. Triyono, SE, M.Si (2016)
This study aims to provide empirical evidence of influence: intangible asset value for the firm value, managerial ownership and institusional ownership for the firm value, and financial performance for the firm value on the company's Manufacturing registered BEI in 2011-2014. The sample in this study were 25 companies listed on the BEI during the period 2011-2014. The analytical method used is multiple linear regression analysis. Results of this study prove that variabel intangible asset value and financial performance on return on asset has significant influence partially on the firm value with a probability value, while variable managerial ownership and institutional ownership, and financial performance on current ratio and asset turnover has no significant effect on the firm value in manufacturing BEI.